Exploring the crowded central region of 10 galactic globular clusters using EMCCDs: variable star searches and new discoveries - Figuera Jaimes, Roberto; Schmidt, Robert W. (Arxiv, 2015)
Obtain time-series photometry of the very crowded central regions of Galactic globular clusters with better angular resolution than previously achieved with conventional CCDs on ground-based telescopes to complete, or improve, the census of the variable star population in those stellar systems. Images were taken using the Danish 1.54-m Telescope at the ESO observatory at La Silla in Chile. The telescope was equipped with an electron-multiplying CCD and the short-exposure-time images obtained (10 images per second) were stacked using the shift-and-add technique to produce the normal-exposure-time images (minutes). Photometry was performed via difference image analysis. Automatic detection of variable stars in the field was attempted. The light curves of 12541 stars in the cores of 10 globular clusters were statistically analysed in order to automatically extract the variable stars. We obtained light curves for 31 previously known variable stars (3 L, 2 SR, 20 RR Lyrae, 1 SX Phe, 3 cataclysmic variables, 1 EW and 1 NC) and we discovered 30 new variables (16 L, 7 SR, 4 RR Lyrae, 1 SX Phe and 2 NC).